DEVELOPING EDUCATIONAL AND INDEPENDENT LEARNING TASKS FOR NEANTOLOGY AS A MEDICAL-PEDAGOGICAL AND METHODOLOGICAL PROBLEM - Anvarova Zilola Qosimovna (The Bioscan, 2025)
In the medical education system, traditional classroom lessons are designed to impart knowledge to students, particularly future medical specialists, to memorize information through educational tasks, and to perform medical analysis of sentences derived from various sources. However, this is increasingly failing to meet the demands of the modern era. Life presents humanity with various problems, and every individual must have the ability to solve them independently. In this context, the technology of problem-based learning has been introduced into medical pedagogy. In problem-based learning, questions and assignments play a crucial role among the educational tasks. The essence of problem-based teaching is that the medical educator does not deliver knowledge in a ready-made form; instead, the medical educator poses problematic tasks in the form of a question or an assignment, prompting the lesson organizer to search for ways and means to solve them. This is also, of course, carried out through questions and assignments. Exercises, on the other hand, mean the repeated performance of a mental or practical action for the purpose of mastering it or improving its quality. Exercises also participate in this process in their own way. Keywords Medical teaching, medical knowledge, high quality, medical service, rheumatism (disease), treatment, description, patient, medical procedure/treatment, medical skill, medical education, educational objective, Bicillin, prophylaxis/prevention, incidence (of disease) and recurrence, remission/decline, streptococcal theory, rheumatism.